High-performance aluminum alloy for photovoltaic panel thin-wall frame and preparation method of high-performance aluminum alloy

By adding main alloy elements such as Mg, Si, Cu, Mn and trace elements such as Ni, Ag, and Ti to the aluminum alloy material, and optimizing the ratio of rare earth elements, the problem of insufficient strength and hardness of existing aluminum alloy materials is solved, significantly improving the material's mechanical properties and corrosion resistance, and reducing the maintenance cost of photovoltaic panel frames.

CN119800175APending Publication Date: 2025-04-11GUANGDONG GUANZHONGYING NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411972986.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When existing aluminum alloy materials are used for solar photovoltaic panel installation, the strength and hardness are low, resulting in severe wear and tear in the field environment and high maintenance costs and labor intensity.

Method used

Develop a high-performance aluminum alloy material, including Mg, Si, Cu, Mn, Ni, Ag, Ti, B, Sm, Eu, Yb and other elements. Through the optimized ratio of rare earth elements and the reasonable addition of trace elements, the strength, hardness and corrosion resistance of the material are improved.

Benefits of technology

The strength and hardness of aluminum alloy materials have been improved, and the neutral salt spray resistance can be up to 500 hours, which significantly reduces the wear and maintenance costs of photovoltaic panel frames.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800175A_ABST
    Figure CN119800175A_ABST
Patent Text Reader

Abstract

The high-performance aluminum alloy comprises the following chemical components in percentage by mass: 0.4 to 1.2 percent of Mg, 0.1 to 1.2 percent of Si, 0.1 to 1.2 percent of Cu, 0.6 to 1.2 percent of Mn, 0.03 to 0.3 percent of Ni, 0.03 to 0.3 percent of Ag, 0.01 to 0.15 percent of Ti, 0.002 to 0.03 percent of B, 0.03 to 0.6 percent of Sm, 0.03 to 0.6 percent of Eu, 0.03 to 0.6 percent of Yb, less than or equal to 0.3 percent of Fe, less than or equal to 0.03 percent of other inevitable single impurity elements, less than or equal to 0.15 percent of total impurity elements and the balance of aluminum. The rare earth element is used as a reinforcing agent, the use amount of the added main alloy elements and transition metal elements is optimally designed, and then the high-performance aluminum alloy is prepared through the technological steps of smelting, casting, hot extrusion, heat treatment, anodic oxidation and the like. The method can be applied to production of photovoltaic panel thin-wall frames and other aluminum alloy structural parts, the service life of the aluminum alloy structural parts is prolonged, the weight of photovoltaic panels is reduced, and cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum alloy materials and photovoltaic panel products, and specifically relates to a high-performance aluminum alloy for a photovoltaic panel thin-wall frame and a preparation method thereof. Background Art

[0002] With the continuous development of social economy, human beings have an increasing demand for new energy, and finding new energy has become a key issue facing mankind. As a kind of clean energy, solar energy has received more and more attention and is currently becoming an important part of my country's new energy structure. The construction and installation of solar photovoltaic panels require a large number of structural parts, including frames, purlins, locks, brackets, etc. Most of these structural parts are currently made of aluminum alloy materials, and their main grades are 6005 and 6063. The advantages of these grades of aluminum alloys are good formability, excellent anodizing performance, and excellent corrosion resistance, but the disadvantages are also very obvious, mainly low strength and hardness, and weak resistance to load disturbances imposed by the environment during use. For example, frames, guide rails and other parts are severely worn during use due to their low hardness and need to be replaced frequently. At present, many solar photovoltaic panels are installed in wild areas, and the maintenance cost and labor intensity caused by replacing parts are high. Therefore, it is urgent to develop an aluminum alloy material that has the same formability, anodizing and corrosion resistance as 6005 and 6063 aluminum alloys, but with higher strength and hardness, so as to ensure the reliable operation of solar photovoltaic panels and reduce maintenance costs and labor intensity. Summary of the invention

[0003] In view of the above-mentioned deficiencies, the present invention discloses a high-performance aluminum alloy for thin-walled frames of photovoltaic panels and a preparation method thereof, develops an aluminum alloy material that has the same formability, anodizing properties and corrosion resistance as 6005 and 6063 aluminum alloys, but with higher strength and hardness, and solves the problems existing in the use of aluminum alloy structural parts for the installation of solar photovoltaic panels.

[0004] The present invention is achieved by adopting the following technical solutions: A high-performance aluminum alloy for a photovoltaic panel thin-wall frame, comprising the following chemical components in mass fractions: Mg: 0.4~1.2%, Si: 0.1~1.2%, Cu: 0.1~1.2%, Mn: 0.6~1.2%, Ni: 0.03~0.3%, Ag: 0.03~0.3%, Ti: 0.01~0.15%, B: 0.002~0.03%, Sm: 0.03~0.6%, Eu: 0.03~0.6%, Yb: 0.03~0.6%, Fe≤0.3%, other unavoidable single impurity elements ≤0.03%, the total amount of impurity elements ≤0.15%, the balance is aluminum.

[0005] The main alloying elements in the aluminum alloy of the present invention mainly include Mg, Si, Cu, and Mn. The addition amount of these four elements in the alloy is relatively high, and they are the main sources of the alloy properties. Among them, Mg and Si elements have the effect of solid solution strengthening on the one hand, and can also form nano-scale β-phase precipitates during artificial aging on the other hand, producing precipitation strengthening; Mn element can mainly change the morphology of Fe-rich phase and improve the plasticity of alloy materials; Cu element is similar to Si and Mg elements, and has the effect of solid solution strengthening on the one hand, and can also produce precipitation strengthening in the form of θ or Q-phase precipitates during artificial aging on the other hand.

[0006] At the same time, the present invention adds appropriate amounts of transition metal elements such as Ni, Ag, and Ti. Among them, the Ni element can form an Al3Ni intermediate phase with the Al element, which is crystallized during the solidification process, and is refined and broken through homogenization and extrusion processing, and is evenly distributed in the alloy, hindering the slip of dislocations and the occurrence of dynamic recrystallization processes; the Ag element can be precipitated together with the Si, Mg, and Cu elements during the artificial aging process to form a π phase, producing a precipitation strengthening effect; the Ti element is added in the alloy liquid flow trough through the aluminum-titanium-boron intermediate alloy, and interacts with the Al and B elements to achieve the effect of refining the grains.

[0007] Moreover, the present invention specifically selects and adds three rare earth elements, namely Sm, Eu and Yb. Sm, Eu and Yb can form intermediate phases such as Al3Sm, Al3Eu and Al3Yb with Al element in aluminum alloy. If all three exist at the same time, they will intermix to form Al3(Sm x ,Eu y ,Yb z ), and x, and z simultaneously satisfy the conditions of x+y+z=1, x≤1, y≤1, and z≤1; on the one hand, these intermediate phases containing rare earth elements crystallize and precipitate during the casting process, resulting in a grain refinement effect; on the other hand, these intermediate phases precipitate and precipitate during the homogenization process, resulting in precipitation strengthening and recrystallization inhibition effects, thereby improving the mechanical properties of the alloy material; thirdly, the rare earth elements can react with the trace H elements in the alloy to form hydrides, converting the free H elements into a combined state, reducing the risk of H elements agglomerating to form hydrogen and causing internal pores.

[0008] Furthermore, the high-performance aluminum alloy for the photovoltaic panel thin-wall frame includes the following chemical components in mass fractions: Mg: 0.4-1.0%, Si: 0.4-1.0%, Cu: 0.4-1.0%, Mn: 0.6-1.0%, Ni: 0.05-0.2%, Ag: 0.03-0.2%, Ti: 0.01-0.12%, B: 0.002-0.025%, Sm: 0.03-0.4%, Eu: 0.03-0.4%, Yb: 0.03-0.4%, Fe≤0.3%, other unavoidable single impurity elements≤0.03%, total impurity elements≤0.15%, balance aluminum. The total content of Sm, Eu and Yb shall not be less than 0.2% and not more than 0.9%, and the content ratio of Sm, Eu and Yb shall be (1-6):(1-4):(1-4).

[0009] The method for preparing the high-performance aluminum alloy for the photovoltaic panel thin-wall frame comprises the following steps: (1) weighing raw materials in proportion, wherein the raw materials include aluminum ingot, electrolytic copper, magnesium ingot, aluminum-manganese master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy; (2) placing aluminum ingots, electrolytic copper, aluminum-manganese master alloy, and aluminum-nickel master alloy in a smelting furnace and stirring at 740-820° C. for the first stage of heat preservation smelting, then adding aluminum-silver master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy and stirring at 730-780° C. for the second stage of heat preservation smelting, and then adding magnesium ingots and stirring at 680-740° C. for the third stage of heat preservation smelting to obtain alloy liquid, sampling from the alloy liquid for chemical composition analysis, if there is a deviation in the composition, adjusting the composition using the raw materials described in step (1) and sampling again for analysis until all elements reach the expected indicators; (3) The alloy liquid obtained in step (2) is refined at 700-780° C. for 50-90 minutes, then allowed to stand and slag removed, and then samples are taken for chemical composition analysis. If there is a deviation in the composition, the raw materials described in step (1) are used to adjust the composition and sample analysis is performed again until all elements reach the expected indicators. After each composition adjustment, refining and standing and slag removal are required, and then sampling and analysis are performed again; (4) releasing the alloy liquid treated in step (3) for casting, with the casting temperature controlled at 660-730° C., and when the alloy liquid is kept warm, an aluminum-titanium-boron master alloy is added to the launder for grain refinement. The alloy liquid is then subjected to double-stage filtration and then passes through a crystallizer into a casting mold for semi-continuous casting to obtain a round rod-shaped ingot; (5) placing the round rod-shaped ingot obtained in step (4) into a heating furnace for homogenization treatment at 450-600° C. for not less than 4 hours, then cutting a section of the round rod-shaped ingot into an extruder to extrude a profile, and cooling the profile from the extruder to room temperature with strong wind, and then straightening the profile and cutting it into a desired length; (6) The profile formed by extrusion in step (5) is placed in an aging furnace for artificial aging treatment. After the artificial aging treatment, the profile is taken out of the furnace and cooled to room temperature. Then, an anodizing treatment is performed to obtain a high-performance aluminum alloy for a thin-walled frame of a photovoltaic panel.

[0010] The obtained high-performance aluminum alloy for the thin-walled frame of the photovoltaic panel can achieve the following performance parameters: yield strength ≥300MPa, tensile strength ≥340MPa, elongation after fracture ≥10.0%, and resistance to neutral salt spray test up to 500 hours.

[0011] Furthermore, in step (1), the contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.5-10.5%. The present invention further adjusts the usage ratio of samarium, europium and ytterbium in the aluminum alloy by controlling the addition amount of the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy, so that they can be doped with each other to form a complex intermediate phase, and can effectively improve the performance of the aluminum alloy, refine the grains, inhibit recrystallization and reduce the risk of H element aggregation to form hydrogen and cause internal pores.

[0012] Furthermore, in step (2), the first stage of heat preservation and melting time is 1 to 5 hours, the second stage of heat preservation and melting time is 1 to 3 hours, and the third stage of heat preservation and melting time is 1 to 3 hours; the stirring speed is 60 to 160 r / min.

[0013] Furthermore, in step (3), the refining gas used in the refining process is high-purity argon gas with a concentration of 99.99%.

[0014] Furthermore, in step (4), the Ti content in the alloy liquid after the addition of the aluminum-titanium-boron master alloy reaches 0.01-0.15%; the first stage of the two-stage filtration uses a 60-mesh ceramic filter plate, and the second stage uses an 80-mesh ceramic filter plate; the descent speed of the crystallizer is 40-240 mm / min.

[0015] Furthermore, in step (5), during the extrusion process of the profile, the extrusion speed is 2 to 12 m / min, and after the profile is extruded from the extruder, it is cooled to room temperature by a strong wind plus spray cooling method, and the cooling speed is 200 to 600°C / min. By controlling the cooling speed, not only the cooling efficiency can be improved, but also the influence of the improper cooling speed on the product performance can be avoided.

[0016] Furthermore, in step (6), the temperature of the artificial aging treatment is 150 to 220° C., and the time of the artificial aging treatment is 3 to 12 hours.

[0017] Compared with the prior art, this technical solution has the following beneficial effects: 1. The present invention utilizes rare earth elements samarium (Sm), europium (Eu), and ytterbium (Yb), and optimizes the ratio between the three, giving full play to the special physical and metallurgical properties of rare earth elements in aluminum alloys to enhance the strength and plasticity of aluminum alloy materials, thereby improving the toughness, fatigue resistance and other indicators of the materials.

[0018] 2. The present invention comprehensively utilizes the effect of Ti, B, Ni and rare earth elements in refining the grains of aluminum alloy, further reducing the grain size of the cast aluminum alloy, and providing good conditions for the alloy material to obtain good performance.

[0019] 3. The present invention utilizes the solid solution strengthening effect produced by the main alloy elements Si, Mg, and Cu and a series of precipitation phases formed between them and the trace element Ag to produce a strengthening effect and improve the comprehensive performance of the alloy material.

[0020] 4. The aluminum alloy material of the present invention has high comprehensive mechanical properties, which can effectively reduce the thickness and weight of the photovoltaic panel frame and improve its service safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a 200-fold metallographic image of the high-performance aluminum alloy cast rod obtained in Example 1 in the cast state.

[0022] Figure 2 This is a 500-fold metallographic image of the high-performance aluminum alloy cast rod obtained in Example 1 after homogenization treatment.

[0023] Figure 3 The metallographic image is 200 times larger than the thin-walled frame of the photovoltaic panel made of the high-performance aluminum alloy of Example 1 in Experimental Example 1.

[0024] Figure 4 This is the stress-strain curve obtained by tensile testing the thin-walled frame of the photovoltaic panel made of the high-performance aluminum alloy of Example 1 in Experimental Example 1. DETAILED DESCRIPTION

[0025] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.

[0026] Embodiment 1: A high-performance aluminum alloy for a photovoltaic panel thin-wall frame, comprising the following chemical components in mass fractions: Mg: 0.83%, Si: 0.94%, Cu: 0.72%, Mn: 0.69%, Ni: 0.10%, Ag: 0.09%, Ti: 0.04%, B: 0.008%, Sm: 0.09%, Eu: 0.18%, Yb: 0.13%, Fe: 0.12%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, the balance is aluminum.

[0027] The method for preparing the high-performance aluminum alloy for the photovoltaic panel thin-wall frame described in this embodiment comprises the following steps: (1) weighing raw materials in proportion, wherein the raw materials include aluminum ingot, electrolytic copper, magnesium ingot, aluminum-manganese master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy; The contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.5-10.5%, and the addition ratio of the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy is 1:2:1.4; (2) taking aluminum ingots, electrolytic copper, aluminum-manganese master alloy, and aluminum-nickel master alloy, and placing them in a smelting furnace and heating them to 780-800°C to melt the charge, and then controlling the temperature at 785°C with stirring to carry out the first stage of heat preservation smelting, and then after the furnace temperature drops to 740-770°C, adding aluminum-silver master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy, and then controlling the temperature at 760°C with stirring to carry out the second stage of heat preservation smelting, and then after the furnace temperature drops to 690-730°C, adding magnesium ingots and controlling the temperature at 720°C with stirring to carry out the third stage of heat preservation smelting to obtain alloy liquid, sampling from the alloy liquid for chemical composition analysis, and if there is a deviation in the composition, adjusting the composition using the raw materials described in step (1) and sampling again for analysis until all elements reach the expected index; The first stage of heat preservation and melting time is 4 hours, the second stage of heat preservation and melting time is 2 hours, and the third stage of heat preservation and melting time is 1.5 hours; the stirring speed is 80r / min; (3) The alloy liquid obtained in step (2) is refined at 715° C. for 60 minutes, then allowed to stand and slag removed, and then samples are taken for chemical composition analysis. If the composition is deviated, the raw materials described in step (1) are used to adjust the composition and sample analysis is performed again until all elements reach the expected indicators. After each composition adjustment, refining and standing and slag removal are required, and then sampling and analysis are performed again; the refining gas used in the refining process is high-purity argon gas with a concentration of 99.99%; (4) releasing the alloy liquid treated in step (3) for casting, the casting temperature being controlled at 689°C, and when the alloy liquid is kept warm, an aluminum-titanium-boron master alloy is added to the flow trough for grain refinement, the Ti content of the alloy liquid after the aluminum-titanium-boron master alloy treatment reaches 0.042%, and then the alloy liquid is subjected to double-stage filtration treatment and then passes through a crystallizer into a casting mold for semi-continuous casting to obtain a round rod-shaped ingot with a diameter of 150 mm; the first stage of the double-stage filtration uses a 60-mesh ceramic filter plate, and the second stage uses an 80-mesh ceramic filter plate; the descending speed of the crystallizer is 124 mm / min; (5) placing the round rod-shaped ingot obtained in step (4) into a heating furnace for homogenization treatment at 545° C. for 6 hours, then cutting a section of the round rod-shaped ingot into an extruder for extrusion into a profile at an extrusion speed of 8 m / min. After the profile is extruded from the extruder, it is cooled to room temperature by a strong wind plus spray cooling method at a cooling rate of 300° C. / min. Then, the profile is straightened and cut into a desired length; (6) placing the extruded profile in step (5) into an aging furnace for artificial aging treatment, taking it out of the furnace after the artificial aging treatment and cooling it to room temperature, and then performing an anodizing treatment to obtain a high-performance aluminum alloy for a photovoltaic panel thin-wall frame; the artificial aging treatment temperature is 168° C., and the artificial aging treatment time is 8 hours.

[0028] Embodiment 2: A high-performance aluminum alloy for a photovoltaic panel thin-wall frame, comprising the following chemical components in mass fractions: Mg: 0.91%, Si: 0.94%, Cu: 1.03%, Mn: 0.84%, Ni: 0.15%, Ag: 0.21%, Ti: 0.10%, B: 0.02%, Sm: 0.13%, Eu: 0.34%, Yb: 0.17%, Fe: 0.10%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, the balance is aluminum.

[0029] The method for preparing the high-performance aluminum alloy for the photovoltaic panel thin-wall frame described in this embodiment comprises the following steps: (1) weighing raw materials in proportion, wherein the raw materials include aluminum ingot, electrolytic copper, magnesium ingot, aluminum-manganese master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy; The contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.5-10.5%, and the addition ratio of the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy is 1.5:4.0:2.0; (2) taking aluminum ingots, electrolytic copper, aluminum-manganese master alloy, and aluminum-nickel master alloy and placing them in a smelting furnace and heating them to 790-820° C. to melt the charge, and then controlling the temperature at 790° C. with stirring to carry out the first stage of heat preservation smelting, and then after the furnace temperature drops to 740-760° C., adding aluminum-silver master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy and controlling the temperature at 750° C. with stirring to carry out the second stage of heat preservation smelting, and then after the furnace temperature drops to 680-720° C., adding magnesium ingots and controlling the temperature at 720° C. with stirring to carry out the third stage of heat preservation smelting to obtain alloy liquid, sampling from the alloy liquid for chemical composition analysis, and if there is a deviation in the composition, adjusting the composition using the raw materials described in step (1) and sampling again for analysis until all elements reach the expected index; The first stage of heat preservation and melting time is 4.5 hours, the second stage of heat preservation and melting time is 2.5 hours, and the third stage of heat preservation and melting time is 1.5 hours; the stirring speed is 120r / min; (3) The alloy liquid obtained in step (2) is refined at 710° C. for 70 minutes, then allowed to stand and slag removed, and then samples are taken for chemical composition analysis. If the composition is deviated, the raw materials described in step (1) are used to adjust the composition and sample analysis is performed again until all elements reach the expected indicators. After each composition adjustment, refining and standing and slag removal are required, and then sampling and analysis are performed again; the refining gas used in the refining process is high-purity argon gas with a concentration of 99.99%; (4) The alloy liquid treated in step (3) is released for casting, and the casting temperature is controlled at 705°C. When the alloy liquid is kept warm, an aluminum-titanium-boron master alloy is added to the flow trough for grain refinement. The Ti content of the alloy liquid after the aluminum-titanium-boron master alloy treatment reaches 0.1%. The alloy liquid is then subjected to double-stage filtration treatment and then passes through a crystallizer into a casting mold for semi-continuous casting to obtain a round rod-shaped ingot with a diameter of 178 mm. The first stage of the double-stage filtration uses a 60-mesh ceramic filter plate, and the second stage uses an 80-mesh ceramic filter plate. The descending speed of the crystallizer is 116 mm / min. (5) placing the round rod-shaped ingot obtained in step (4) into a heating furnace for homogenization treatment at 555° C. for 5 hours, then cutting a section of the round rod-shaped ingot into an extruder to extrude a profile at a speed of 4 m / min. After the profile is extruded from the extruder, it is cooled to room temperature by a strong wind plus spray cooling method at a cooling rate of 360° C. / min. Then, the profile is straightened and cut into a desired length; (6) The profile formed by extrusion in step (5) is placed in an aging furnace for artificial aging treatment. After the artificial aging treatment, the profile is taken out of the furnace and cooled to room temperature. Then, the profile is anodized to obtain a high-performance aluminum alloy for a thin-walled frame of a photovoltaic panel. The temperature of the artificial aging treatment is 178° C., and the time of the artificial aging treatment is 6 hours.

[0030] Embodiment 3: A high-performance aluminum alloy for a photovoltaic panel thin-wall frame, comprising the following chemical components in mass fractions: Mg: 0.76%, Si: 0.84%, Cu: 0.62%, Mn: 0.98%, Ni: 0.16%, Ag: 0.17%, Ti: 0.08%, B: 0.01%, Sm: 0.17%, Eu: 0.23%, Yb: 0.18%, Fe: 0.15%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, the balance is aluminum.

[0031] The method for preparing the high-performance aluminum alloy for the photovoltaic panel thin-wall frame described in this embodiment comprises the following steps: (1) weighing raw materials in proportion, wherein the raw materials include aluminum ingot, electrolytic copper, magnesium ingot, aluminum-manganese master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy; The contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.5-10.5%, and the addition ratio of the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy is 1:1.4:1; (2) taking aluminum ingots, electrolytic copper, aluminum-manganese master alloy, and aluminum-nickel master alloy and placing them in a smelting furnace and heating them to 750-780°C to melt the charge, then controlling the temperature at 760°C with stirring to carry out the first stage of heat preservation smelting, then after the furnace temperature drops to 730-760°C, adding aluminum-silver master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy and controlling the temperature at 74-80°C with stirring to carry out the second stage of heat preservation smelting, then after the furnace temperature drops to 680-720°C, adding magnesium ingots and controlling the temperature at 730°C with stirring to carry out the third stage of heat preservation smelting to obtain alloy liquid, sampling from the alloy liquid for chemical composition analysis, if there is a deviation in the composition, adjusting the composition using the raw materials described in step (1) and sampling again for analysis until all elements reach the expected index; The first stage of heat preservation and melting time is 4.5 hours, the second stage of heat preservation and melting time is 2.5 hours, and the third stage of heat preservation and melting time is 1 hour; the stirring speed is 120r / min; (3) The alloy liquid obtained in step (2) is refined at 725° C. for 60 minutes, then allowed to stand and slag removed, and then samples are taken for chemical composition analysis. If the composition is deviated, the raw materials described in step (1) are used to adjust the composition and sample analysis is performed again until all elements reach the expected indicators. After each composition adjustment, refining and standing and slag removal are required, and then sampling and analysis are performed again; the refining gas used in the refining process is high-purity argon gas with a concentration of 99.99%; (4) The alloy liquid treated in step (3) is released for casting, and the casting temperature is controlled at 712°C. When the alloy liquid is kept warm, an aluminum-titanium-boron master alloy is added to the flow trough for grain refinement. The Ti content of the alloy liquid after the aluminum-titanium-boron master alloy treatment reaches 0.08%. Then, the alloy liquid is subjected to double-stage filtration treatment and then passes through a crystallizer into a casting mold for semi-continuous casting to obtain a round rod-shaped ingot with a diameter of 150 mm; the double-stage 154 mm / min; (5) placing the round rod-shaped ingot obtained in step (4) into a heating furnace for homogenization treatment at 560° C. for 5 hours, then cutting a section of the round rod-shaped ingot into an extruder for extrusion into a profile at an extrusion speed of 6 m / min. After the profile is extruded from the extruder, it is cooled to room temperature by a strong wind plus spray cooling method at a cooling rate of 400° C. / min. Then, the profile is straightened and cut into a desired length; (6) The profile formed by extrusion in step (5) is placed in an aging furnace for artificial aging treatment. After the artificial aging treatment, the profile is taken out of the furnace and cooled to room temperature. Then, the profile is anodized to obtain a high-performance aluminum alloy for a thin-walled frame of a photovoltaic panel. The temperature of the artificial aging treatment is 185° C., and the time of the artificial aging treatment is 3 hours.

[0032] Embodiment 4: A high-performance aluminum alloy for a photovoltaic panel thin-wall frame, comprising the following chemical components in mass fractions: Mg: 0.6%, Si: 0.93%, Cu: 0.1%, Mn: 0.6%, Ni: 0.03%, Ag: 0.03%, Ti: 0.01%, B: 0.002%, Sm: 0.13%, Eu: 0.36%, Yb: 0.28%, Fe: 0.2%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, the balance is aluminum.

[0033] The method for preparing the high-performance aluminum alloy for the photovoltaic panel thin-wall frame described in this embodiment comprises the following steps: (1) weighing raw materials in proportion, wherein the raw materials include aluminum ingot, electrolytic copper, magnesium ingot, aluminum-manganese master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy; The contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.5-10.5%, and the addition ratio of the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy is 1:2.8:2.2; (2) taking aluminum ingots, electrolytic copper, aluminum-manganese master alloy, and aluminum-nickel master alloy, and placing them in a smelting furnace and heating them to 730-750° C. to melt the charge, and then controlling the temperature at 740° C. with stirring to carry out the first stage of heat preservation smelting, and then adding aluminum-silver master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy and controlling the temperature at 730° C. with stirring to carry out the second stage of heat preservation smelting, and then after the furnace temperature drops to 670-690° C., adding magnesium ingots and controlling the temperature at 680° C. with stirring to carry out the third stage of heat preservation smelting to obtain alloy liquid, and sampling from the alloy liquid for chemical composition analysis. If there is a deviation in the composition, the raw materials described in step (1) are used to adjust the composition and sample again for analysis until all elements reach the expected indicators; The first stage of heat preservation and melting time is 3.5 hours, the second stage of heat preservation and melting time is 1.5 hours, and the third stage of heat preservation and melting time is 1.5 hours; the stirring speed is 90r / min; (3) The alloy liquid obtained in step (2) is refined at 680° C. for 90 minutes, then allowed to stand and slag removed, and then samples are taken for chemical composition analysis. If the composition is deviated, the raw materials described in step (1) are used to adjust the composition and sample analysis is performed again until all elements reach the expected indicators. After each composition adjustment, refining and standing and slag removal are required, and then sampling and analysis are performed again; the refining gas used in the refining process is high-purity argon gas with a concentration of 99.99%; (4) The alloy liquid treated in step (3) is released for casting, and the casting temperature is controlled at 660°C. When the alloy liquid is kept warm, an aluminum-titanium-boron master alloy is added to the flow trough for grain refinement. The Ti content of the alloy liquid after the aluminum-titanium-boron master alloy treatment reaches 0.01%. The alloy liquid is then subjected to double-stage filtration treatment and then passes through a crystallizer into a casting mold for semi-continuous casting to obtain a round rod-shaped ingot with a diameter of 100 mm. The first stage of the double-stage filtration uses a 60-mesh ceramic filter plate, and the second stage uses an 80-mesh ceramic filter plate. The descending speed of the crystallizer is 40 mm / min. (5) placing the round rod-shaped ingot obtained in step (4) into a heating furnace for homogenization treatment at 450° C. for 8 hours, then cutting a section of the round rod-shaped ingot into an extruder to extrude a profile at a speed of 2 m / min. After the profile is extruded from the extruder, it is cooled to room temperature by a strong wind plus spray cooling method at a cooling rate of 460° C. / min. Then, the profile is straightened and cut into a desired length; (6) The profile formed by extrusion in step (5) is placed in an aging furnace for artificial aging treatment. After the artificial aging treatment, the profile is taken out of the furnace and cooled to room temperature, and then anodized to obtain a high-performance aluminum alloy for a thin-walled frame of a photovoltaic panel; the temperature of the artificial aging treatment is 150° C., and the time of the artificial aging treatment is 12 hours.

[0034] Embodiment 5: A high-performance aluminum alloy for a photovoltaic panel thin-wall frame, comprising the following chemical components in mass fractions: Mg: 0.69%, Si: 0.84%, Cu: 1.2%, Mn: 1.2%, Ni: 0.3%, Ag: 0.3%, Ti: 0.15%, B: 0.03%, Sm: 0.2%, Eu: 0.21%, Yb: 0.19%, Fe: 0.2%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, the balance is aluminum.

[0035] The method for preparing the high-performance aluminum alloy for the photovoltaic panel thin-wall frame described in this embodiment comprises the following steps: (1) weighing raw materials in proportion, wherein the raw materials include aluminum ingot, electrolytic copper, magnesium ingot, aluminum-manganese master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy; The contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.5-10.5%, and the addition ratio of the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy is 1:1:1; (2) taking aluminum ingots, electrolytic copper, aluminum-manganese master alloy, and aluminum-nickel master alloy and placing them in a smelting furnace and heating them to 790-820° C. to melt the charge, and then stirring at 820° C. to carry out the first stage of heat preservation smelting, and then after the furnace temperature drops to 770-790° C., adding aluminum-silver master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy and stirring at 780° C. to carry out the second stage of heat preservation smelting, and then after the furnace temperature drops to 720-740° C., adding magnesium ingots and stirring at 740° C. to carry out the third stage of heat preservation smelting to obtain alloy liquid, sampling from the alloy liquid for chemical composition analysis, if there is a deviation in the composition, adjusting the composition using the raw materials described in step (1) and sampling again for analysis until all elements reach the expected index; The first stage of heat preservation and melting time is 4 hours, the second stage of heat preservation and melting time is 2 hours, and the third stage of heat preservation and melting time is 2 hours; the stirring speed is 80r / min; (3) The alloy liquid obtained in step (2) is refined at 740° C. for 50 minutes, then allowed to stand and slag removed, and then samples are taken for chemical composition analysis. If the composition is deviated, the raw materials described in step (1) are used to adjust the composition and sample analysis is performed again until all elements reach the expected indicators. After each composition adjustment, refining and standing and slag removal are required, and then sampling and analysis are performed again; the refining gas used in the refining process is high-purity argon gas with a concentration of 99.99%; (4) releasing the alloy liquid treated in step (3) for casting, the casting temperature being controlled at 730°C, and when the alloy liquid is kept warm, an aluminum-titanium-boron master alloy is added to the flow trough for grain refinement, the Ti content of the alloy liquid after the aluminum-titanium-boron master alloy treatment reaches 0.15%, and then the alloy liquid is subjected to double-stage filtration treatment and then passes through a crystallizer into a casting mold for semi-continuous casting to obtain a round rod-shaped ingot with a diameter of 150 mm; the first stage of the double-stage filtration uses a 60-mesh ceramic filter plate, and the second stage uses an 80-mesh ceramic filter plate; the descending speed of the crystallizer is 240 mm / min; (5) placing the round rod-shaped ingot obtained in step (4) into a heating furnace for homogenization treatment at 600° C. for 4 hours, then cutting a section of the round rod-shaped ingot into an extruder to extrude a profile at an extrusion speed of 12 m / min. After the profile is extruded from the extruder, it is cooled to room temperature by a strong wind plus spray cooling method at a cooling rate of 500° C. / min. Then, the profile is straightened and cut into a desired length; (6) The profile formed by extrusion in step (5) is placed in an aging furnace for artificial aging treatment. After the artificial aging treatment, the profile is taken out of the furnace and cooled to room temperature. Then, the profile is anodized to obtain a high-performance aluminum alloy for a thin-walled frame of a photovoltaic panel. The temperature of the artificial aging treatment is 220° C., and the time of the artificial aging treatment is 3 hours.

[0036] Comparative Example 1: A photovoltaic panel frame made of 6005A aluminum alloy is used for comparison. The 6005A aluminum alloy is made into corresponding extruded profiles through melting and casting, hot extrusion, solution treatment, and artificial aging.

[0037] Comparative Example 2: A photovoltaic panel frame made of 6063 aluminum alloy is used for comparison. The 6063 aluminum alloy is made into corresponding extruded profiles through melting and casting, hot extrusion, solution treatment and artificial aging.

[0038] Experimental Example 1: Photovoltaic panel frames were prepared according to the methods described in Examples 1 to 5 and Comparative Examples 1 to 2, and their performance tests were performed. The specific tests are as follows: Room temperature mechanical properties test: According to GB / T 228.1-2010 “Tensile tests on metallic materials Part 1: Room temperature test methods”, samples were taken at random positions on the frame of the photovoltaic panel and machined into tensile specimens, which were then tested on a tensile testing machine. The results are shown in Table 1.

[0039] Table 1 Test results of mechanical properties of photovoltaic panel frame materials

[0040] It can be seen from Table 1 that the yield strength, tensile strength and elongation of the photovoltaic panel frame profile obtained by the present invention are higher than those of the photovoltaic panel frame profile made of 6005A and 6063 aluminum alloys.

[0041] Experimental Example 2: A rare earth element enhanced aluminum alloy material was prepared according to the method described in Examples 1 to 5, and the aluminum alloy material described in Comparative Examples 1 to 2 was used as a control to detect the crystal structure and lattice parameters of the aluminum alloy material. The results are shown in Table 2.

[0042] Table 2 Test results of aluminum alloy materials

[0043] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-performance aluminum alloy for a photovoltaic panel thin-wall frame, characterized by: The chemical components include the following mass fractions: Mg: 0.4~1.2%, Si: 0.1~1.2%, Cu: 0.1~1.2%, Mn: 0.6~1.2%, Ni: 0.03~0.3%, Ag: 0.03~0.3%, Ti: 0.01~0.15%, B: 0.002~0.03%, Sm: 0.03~0.6%, Eu: 0.03~0.6%, Yb: 0.03~0.6%, Fe≤0.3%, other unavoidable single impurity elements ≤0.03%, the total amount of impurity elements ≤0.15%, the balance is aluminum.

2. The high-performance aluminum alloy for photovoltaic panel thin-walled frame according to claim 1 is characterized in that: The high-performance aluminum alloy for the photovoltaic panel thin-wall frame includes the following chemical components by mass fraction: Mg: 0.4~1.0%, Si: 0.4~1.0%, Cu: 0.4~1.0%, Mn: 0.6~1.0%, Ni: 0.05~0.2%, Ag: 0.03~0.2%, Ti: 0.01~0.12%, B: 0.002~0.025%, Sm: 0.03~0.4%, Eu: 0.03~0.4%, Yb: 0.03~0.4%, Fe≤0.3%, other unavoidable single impurity elements ≤0.03%, the total amount of impurity elements ≤0.15%, the balance is aluminum.

3. The method for preparing a high-performance aluminum alloy for a photovoltaic panel thin-wall frame as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) weighing raw materials in proportion, wherein the raw materials include aluminum ingot, electrolytic copper, magnesium ingot, aluminum-manganese master alloy, aluminum-nickel master alloy, aluminum-silver master alloy, aluminum-titanium-boron master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy; (2) placing aluminum ingots, electrolytic copper, aluminum-manganese master alloy, and aluminum-nickel master alloy in a smelting furnace and stirring at 740-820° C. for the first stage of heat preservation smelting, then adding aluminum-silver master alloy, aluminum-samarium master alloy, aluminum-europium master alloy, and aluminum-ytterbium master alloy and stirring at 730-780° C. for the second stage of heat preservation smelting, and then adding magnesium ingots and stirring at 680-740° C. for the third stage of heat preservation smelting to obtain alloy liquid, sampling from the alloy liquid for chemical composition analysis, if there is a deviation in the composition, adjusting the composition using the raw materials described in step (1) and sampling again for analysis until all elements reach the expected indicators; (3) The alloy liquid obtained in step (2) is refined at 700-780° C. for 50-90 minutes, then allowed to stand and slag removed, and then samples are taken for chemical composition analysis. If there is a deviation in the composition, the raw materials described in step (1) are used to adjust the composition and sample analysis is performed again until all elements reach the expected indicators. After each composition adjustment, refining and standing and slag removal are required, and then sampling and analysis are performed again; (4) releasing the alloy liquid treated in step (3) for casting, with the casting temperature controlled at 660-730° C., and when the alloy liquid is kept warm, an aluminum-titanium-boron master alloy is added to the launder for grain refinement. The alloy liquid is then subjected to double-stage filtration and then passes through a crystallizer into a casting mold for semi-continuous casting to obtain a round rod-shaped ingot; (5) placing the round rod-shaped ingot obtained in step (4) into a heating furnace for homogenization treatment at 450-600° C. for not less than 4 hours, then cutting a section of the round rod-shaped ingot into an extruder to extrude a profile, and cooling the profile from the extruder to room temperature with strong wind, and then straightening the profile and cutting it into a desired length; (6) The profile formed by extrusion in step (5) is placed in an aging furnace for artificial aging treatment. After the artificial aging treatment, the profile is taken out of the furnace and cooled to room temperature. Then, an anodizing treatment is performed to obtain a high-performance aluminum alloy for a thin-walled frame of a photovoltaic panel.

4. The method for preparing a high-performance aluminum alloy for a photovoltaic panel thin-wall frame according to claim 3, characterized in that: In step (1), the contents of samarium, europium and ytterbium in the aluminum-samarium master alloy, the aluminum-europium master alloy and the aluminum-ytterbium master alloy are all 9.5-10.5%.

5. The method for preparing a high-performance aluminum alloy for a photovoltaic panel thin-wall frame according to claim 3, characterized in that: In step (2), the first stage of heat preservation and melting time is 1 to 5 hours, the second stage of heat preservation and melting time is 1 to 3 hours, and the third stage of heat preservation and melting time is 1 to 3 hours; the stirring speed is 60 to 160 r / min.

6. The method for preparing a high-performance aluminum alloy for a photovoltaic panel thin-wall frame according to claim 3, characterized in that: In step (3), the refining gas used in the refining process is high-purity argon gas with a concentration of 99.99%.

7. The method for preparing a high-performance aluminum alloy for a photovoltaic panel thin-wall frame according to claim 3, characterized in that: In step (4), the Ti content in the alloy liquid after the aluminum-titanium-boron master alloy treatment reaches 0.01-0.15%; the first stage of the two-stage filtration uses a 60-mesh ceramic filter plate, and the second stage uses an 80-mesh ceramic filter plate; the descent speed of the crystallizer is 40-240 mm / min.

8. The method for preparing a high-performance aluminum alloy for a photovoltaic panel thin-wall frame according to claim 3, characterized in that: In step (5), during the extrusion process of the profile, the extrusion speed is 2 to 14 m / min. After the profile is extruded from the extruder, it is cooled to room temperature by a strong wind and spray cooling method, and the cooling rate is 200 to 600°C / min.

9. The method for preparing a high-performance aluminum alloy for a photovoltaic panel thin-wall frame according to claim 3, characterized in that: In step (6), the temperature of the artificial aging treatment is 150 to 220° C., and the time of the artificial aging treatment is 3 to 12 hours.